Peran Badan Pusat Statistik dalam Mendukung Literasi Data Dikalangan Mahasiswa - Aminatus Zahriyah; Tia Rahel Amanda; Anis Fitryah; Zuhriyah Zulian Nihrir (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
In the current era of rapid information development, data literacy has become an essential skill, particularly for students. The Central Statistics Agency (BPS) plays a crucial role in enhancing data literacy among students by providing accurate and relevant statistical data and information. This study aims to explore BPS's contributions to supporting data literacy development in academic environments. Using a descriptive qualitative method, this research collects data through in-depth interviews, participatory observations, and document analysis to understand how students utilize statistical data in their studies. The findings indicate that BPS not only functions as a data provider but also acts as a catalyst for statistical education through various mentoring programs and collaborations with educational institutions. These programs include public lectures, workshops, and the establishment of "Statistical Corners," which offer direct access for students to receive guidance in understanding and utilizing data. Despite progress in statistical literacy, challenges remain, such as students' difficulties in critically evaluating information sources. This research also finds that direct interaction with statisticians can enhance students' confidence and analytical skills. With the increasing penetration of the internet and the use of social media, students need to be equipped with skills to access and effectively utilize information. Therefore, innovative approaches are required to improve understanding of information technology usage among students. The results of this study are expected to provide valuable insights for further developing strategies to enhance statistical literacy in academic settings, as well as reinforcing BPS's role as an active data provider in building human resource capacity in Indonesia.